HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN KIMIA KELAS XI IPA SMA NEGERI DI KOTA MAKASSAR - Arwien, Rizki Trisnawaty (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2021)
This research was conducted with the aim of knowing the correlation of emotional intelligence toward students learning outcomes on Chemistry subject grade XI at SMAN in Makassar. This type of research is an ex post facto-correlational. The population was all student of SMAN grade XII IPA in Makassar. The sample of this research was taken using stratified random sampling technique and the selected school was SMAN 2, SMAN 3, SMAN 5, SMAN 8, SMAN 11, SMAN 14. The data collection technique of this research by using emotional intelligence questionnary and acid base subject test. The data analyzed by descriptive and inferential analysis technique. Hypothesis test by SPPSS 20.0 version which using correlation analysis. Significant score of emotional intelligence with learning outcomes of student is 0,016<0.05 , that shows H1 is accepted and Ho is rejected. This research showing there is correlation between emotional intelligence with student learning outcomes